2022
DOI: 10.1021/acs.jpcc.1c09646
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Fine Structure in C 1s High-Resolution Core-Level Spectra of CO Chemisorbed on Ir(111)

Abstract: The vibrational features of carbon monoxide (CO) adsorbed on Ir(111) were studied by means of high-resolution core-level spectroscopy. By monitoring the Ir 4f 7/2 core level as a function of exposure, we proved that the CO adsorbs on the surface always in on-top sites, in agreement with the results of vibrational spectroscopy techniques and density functional theory studies. The C 1s vibrational splittings measured for the p(√3 × √3)R30°(233.4 ± 0.5 meV) and c(4 × 2√3)rect (231.4 ± 0.4 meV) structures were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…CO adsorption on Ir(111) has been studied for over 50 years by experimental surface science techniques such as low-energy electron diffraction (LEED), Auger electron spectroscopy (AES), temperature-programmed desorption (TPD), Fourier transform infrared reflection-adsorption spectroscopy (FT-IRAS), X-ray photoelectron spectroscopy (XPS), and sum frequency generation (SFG) spectroscopy, 1 , 4 , 18 26 as well as by density functional theory (DFT). 24 , 27 , 28 Two distinct LEED patterns indicated an ordered structure at 1/3 ML 1 , 17 19 and a (diffuse) pattern at high coverage (7/12 ML 19 and 2/3 ML 1 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO adsorption on Ir(111) has been studied for over 50 years by experimental surface science techniques such as low-energy electron diffraction (LEED), Auger electron spectroscopy (AES), temperature-programmed desorption (TPD), Fourier transform infrared reflection-adsorption spectroscopy (FT-IRAS), X-ray photoelectron spectroscopy (XPS), and sum frequency generation (SFG) spectroscopy, 1 , 4 , 18 26 as well as by density functional theory (DFT). 24 , 27 , 28 Two distinct LEED patterns indicated an ordered structure at 1/3 ML 1 , 17 19 and a (diffuse) pattern at high coverage (7/12 ML 19 and 2/3 ML 1 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…CO adsorption on Ir(111) has been studied for over 50 years by experimental surface science techniques such as low-energy electron diffraction (LEED), Auger electron spectroscopy (AES), temperature-programmed desorption (TPD), Fourier transform infrared reflection-adsorption spectroscopy (FT-IRAS), X-ray photoelectron spectroscopy (XPS), and sum frequency generation (SFG) spectroscopy, ,, as well as by density functional theory (DFT). ,, Two distinct LEED patterns indicated an ordered structure at 1/3 ML , and a (diffuse) pattern at high coverage (7/12 ML and 2/3 ML , ). With increasing CO coverage, FT-IRAS showed that the IR spectral intensities of linearly (on-top) bonded CO increased and vibrational frequencies blue-shifted, , while in TPD, the desorption peaks shifted to lower temperature and different adsorption states formed, especially close to saturation. Such observations/trends are quite common for CO adsorption on metals, but we could recently demonstrate that upon increasing the coverage, CO was tilted on Ir(111) [at 0.77 ML by about 20° (DFT) or 36° (SFG)] .…”
Section: Introductionmentioning
confidence: 99%
“…This indicates significant interaction between the Bo χ 6 polymorph and Ir(111), since a similar reduction of the Ir S peak is detected after adsorption of strongly bound species to the Ir surface. 27,28 In contrast, for weakly interacting epitaxial layers, such as graphene or hBN on Ir(111), 24,29 the surface component is almost unaltered in the presence of the 2D overlayer. Possible origin of the relatively small surface component which persists in our sample could be in the fraction of the Ir surface which is left uncovered after the Bo synthesis, considering the recent microspot XPS examination of Bo/Ir where only bulk Ir 4f peaks have been detected.…”
Section: ■ Resultsmentioning
confidence: 99%